In Vitro Safety, Off-Target and Bioavailability Profile of the Antiviral Compound Silvestrol - Susanne Schiffmann; Sandra Gunne; Thomas Ulshöfer; Marina Henke; Luise A. Roser; Ann-Kathrin Schneider; Jindrich Cinatl; Dominique Thomas; Yannick Schreiber; Pia Viktoria Wagner; Arnold Grünweller; Michael J. Parnham (MDPI AG, 2022)
We characterized the in vitro safety and bioavailability profile of silvestrol, a compound effective against various viruses, such as corona- and Ebolaviruses, with an EC50 value of about 5 nM. The cytotoxic profile of silvestrol was assessed in various cancer cell lines, as well as the mutagenic and genotoxic potential with Ames and micronuclei tests, respectively. To identify off-target effects, we investigated whether silvestrol modulates G-protein coupled receptor (GPCR) signaling pathways. To predict the bioavailability of silvestrol, its stability, permeability and cellular uptake were determined. Silvestrol reduced viability in a cell-type-dependent manner, mediated no off-target effects via GPCRs, had no mutagenic potential and minor genotoxic effects at 50 nM. Silvestrol did not disturb cell barrier integrity, showed low membrane permeability, was stable in liver microsomes and exhibited good cellular uptake. Efficient cellular uptake and increased cytotoxicity were observed in cell lines with a low expression level of the transport protein P-glycoprotein, the known efflux transporter of silvestrol. In conclusion, silvestrol showed low permeability but good cellular uptake and high stability. Cell-type-dependent cytotoxicity seems to be caused by the accumulation of silvestrol in cells lacking the ability to expel silvestrol due to low P-glycoprotein levels.